2020
DOI: 10.7150/jca.33029
|View full text |Cite
|
Sign up to set email alerts
|

Metformin and LW6 impairs pancreatic cancer cells and reduces nuclear localization of YAP1

Abstract: The poor survival rate of pancreatic cancer is still a major challenge for the clinicians and their patients. In this study, we evaluated the efficacy of metformin, an inhibitor of oxidative phosphorylation, in combination with LW6, which impairs malate dehydrogenase 2 activities, in treating pancreatic cancer cells. We observed that this combinational therapy significantly reduced cell proliferation, migration, and significantly induced cell death when compared to cells treated by each monotherapy or Sham. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…3 Our overall analysis showed that diabetic patients with metformin use had a significantly reduced risk of HCC (relative risk 0.24, 95% confidence interval 0.13-0.46). These results were supported by experimental studies and multiple potential anti-cancer mechanisms of metformin were proposed, 3,[8][9][10] including inhibition of cell proliferation and hepatic gluconeogenesis, activation of AMPK, and modulation of microRNAs expression.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…3 Our overall analysis showed that diabetic patients with metformin use had a significantly reduced risk of HCC (relative risk 0.24, 95% confidence interval 0.13-0.46). These results were supported by experimental studies and multiple potential anti-cancer mechanisms of metformin were proposed, 3,[8][9][10] including inhibition of cell proliferation and hepatic gluconeogenesis, activation of AMPK, and modulation of microRNAs expression.…”
Section: Introductionmentioning
confidence: 62%
“…3 Epidemiological studies have demonstrated that treatment with metformin can reduce the risk of some cancers, such as HCC, breast cancer, colorectal cancer and pancreatic cancer. [8][9][10] For the association of metformin use with HCC risk, we have published one meta-analysis which included seven studies and 16,549 diabetic patients. 3 Our overall analysis showed that diabetic patients with metformin use had a significantly reduced risk of HCC (relative risk 0.24, 95% confidence interval 0.13-0.46).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the OXPHOS inhibitors could be used to target cancer cell metabolism in PAAD where OXPHOS is upregulated. Interestingly, recent observation revealed YAP1 was involved in the anti-cancer effect of OXPHOS inhibitors (metformin plus LW6) [ 36 ]. In the study, the authors demonstrated that metformin in combination with LW6 impaired pancreatic cancer cells and inhibited nuclear localization of YAP1 by phosphorylation of YAP1 at serine 127.…”
Section: Discussionmentioning
confidence: 99%
“…PAAD is the most aggressive and fatal tumor [ 20 , 21 ]. Due to the lack of a sensitive and specific test of PAAD, the tumors have already spread from the pancreas to the liver and lung [ 22 ]. Thus, it needs to develop a novel test that can diagnose PAAD at an early stage and monitor the treatment response.…”
Section: Discussionmentioning
confidence: 99%